Investigation of the corrosive properties of phase change materials in contact with metals and plastic. (August 2017) - Browne, Maria C.; Boyd, Ellen; McCormack, Sarah J.
Abstract: Phase change material (PCM) is used as a means of storing thermal energy. The method of PCM containment in thermal energy storage (TES) systems is important as the material is in direct contact with metal piping, plates and housing units which can be damaged if the material is corrosive. The compatibility of PCM with various materials for use in TES applications has been investigated using the immersion corrosion method and suggestions to minimise their corrosive behaviour or to mitigate it by using an alternative PCM have been presented and are described in the following paper. The metals and plastics tested were copper, brass, aluminium, stainless steel, mild steel and Perspex. These were immersed in five different PCM, three fatty acids, a salt hydrate and Micronal ® for a period of 722 days. Stainless steel was determined to be the most suitable of all the PCM investigated. Aluminium can be used with all fatty acids, however caution is advised as the maximum corrosion rate was found to be 12.4 m g/cm 2 year. Copper and brass can be encapsulated using fatty acid and again caution is advised as corrosion rates were found to be 22.15 g/cm 2 year and 1.67 g/cm 2 year, respectively. Highlights: A material assessment was carried out on five phase change materials and six commonly used materials. The tests lasted for a period of 722 days. Corrosion rate, mass loss and SEM images of material samples are presented. Stainless steel was found to be the most resistant to corrosion. Depending on the application Perspex could be used to contain PCM if it was required to retain the stored heat.